Analysis of the Impact of Inventory Management Practice on the Effectiveness of Retail Stores in South Africa (Global Journal of Management and Business Research, 2022)
The study analyses the impact of inventory management practice on the effectiveness of retail stores in Vhembe District South Africa A quantitative survey research design was adopted for the study The study used simple random sampling method to collect data from 30 retail stores Results from the study revealed that inventory management tools and techniques like economic order quantity just in time bar coding and inventory management software have a positive effect on the performance of retail stores
Keywords: inventory; inventory management; modern management tools; retail store; south africa